Global Capitalism and the Restructuring of Education: The Transnational Capitalist Class' Quest to Suppress Critical Thinking. - Robinson, William I. (Social Justice, 2016)
As globalization has advanced there has been a dual process in the subordination of global labor. One mass of humanity has been dispossessed, marginalized, and locked out of productive participation in the global economy, while another has been incorporated or reincorporated into capitalist production under new, precarious, and highly exploitative capital-labor arrangements, often engaged in deskilled work that requires little more than basic numeracy and literacy skills. Transnational capital faces the challenge of imposing a system of global education that imparts just enough skills to supply the labor needed by the economy and at the same time transmits an ideological content that compels conformity and undercuts critical thinking.